2001
DOI: 10.1046/j.1460-9568.2001.01549.x
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian homologue of the novel peptide Bv8 is expressed in the central nervous system and supports neuronal survival by activating the MAP kinase/PI‐3‐kinase pathways

Abstract: Previous studies have identified the mammalian homologue of Bv8 (mBv8), a small protein originally isolated from skin secretions of the frog, Bombina variegata. In situ hybridization showed that mBv8 RNA was widely expressed in the rodent CNS, with high levels being detected in layer II of the cerebral cortex, limbic regions, cerebellar Purkinje cells, and dorsal and ventral horns of the spinal cord. A similar pattern of distribution was found by examining the presence of mBv8 protein by immunocytochemistry. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 28 publications
3
77
2
Order By: Relevance
“…None of the tested Bv8 concentrations produced any significant increase in the release of LDH when added alone to the incubation media (data not shown). Because it has been reported that Bv8 may support neuronal survival by activating the MAP-kinase/PI-3 kinase pathways (Melchiorri et al, 2001), we analyzed by Western blot the phophorylation of ERK 1/2, Akt and GSK3-b in cultures treated with Bv8 (10 nM). Bv8 produced significant increases in the phosphorylation of ERK 1/2 and Akt and a more robust increase in the phosphorylation of GSK3-b (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…None of the tested Bv8 concentrations produced any significant increase in the release of LDH when added alone to the incubation media (data not shown). Because it has been reported that Bv8 may support neuronal survival by activating the MAP-kinase/PI-3 kinase pathways (Melchiorri et al, 2001), we analyzed by Western blot the phophorylation of ERK 1/2, Akt and GSK3-b in cultures treated with Bv8 (10 nM). Bv8 produced significant increases in the phosphorylation of ERK 1/2 and Akt and a more robust increase in the phosphorylation of GSK3-b (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These two peptides are highly conserved across species (LeCouter et al, 2004;Giannini et al, 2009) and activate two highly homologous receptors, prokineticin receptor 1 (PKR1) and PKR2 (Negri and Lattanzi, 2011), which are coupled to a variety of G proteins and hence to intracellular Ca 2þ mobilization and activation of the ERK1/2 and Akt pathways (Lin et al, 2002;Masuda et al, 2002;Soga et al, 2002). Prokineticins (especially PK2) and their receptors are largely expressed in CNS (Cheng et al, 2006) and regulate multiple biological functions in the CNS including hyperalgesia (Mollay et al, 1999), neurogenesis in the olfactory bulb (Ng et al, 2005), neuronal survival (Melchiorri et al, 2001) and inflammation (Martucci et al, 2006). Recent studies have implicated PK2 in human diseases such as, for example, Kallmann syndrome, which can be determined by loss-offunction mutations in the gene encoding for PK2 (Pitteloud et al, 2007) or CNS autoimmune demyelination, in which PK2 has been identified as a critical immune regulator (Abou-Hamdan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, we generated antisense and sense riboprobes containing the coding region of rat PK-2 and PKR-2 (GenBank accession numbers AY089984 and AY089975; Melchiorri et al, 2001), labelled them with 35S and processed in situ hybridization as described by Seidman (1999). Radioactivity was detected by coating slides (20-mm sections) with Hypercoat LM-1 emulsion (Amersham Biosciences, Milan, Italy).…”
Section: Food and Water Intakementioning
confidence: 99%
“…Common structural motives in this peptide family are the amino-terminal sequence of 20 amino-acid residues and the five disulphide bonds that link the 10 cysteine residues and fold the molecules into a globular form. The distribution of mRNAs of murine Bv8-like proteins has been reported in the brain, spinal cord, gastrointestinal tract, endocrine glands and other peripheral organs of mice and rats LeCouter et al, 2001;Li et al, 2001;Melchiorri et al, 2001;Cheng et al, 2002;Masuda et al, 2002). In the brain, the main localizations of mPK-2 include the olfactory bulb, cerebral cortex (in some neurones of layer II), dorsal and ventral hippocampus, medial preoptic area of the hypothalamus, suprachiasmatic nucleus (SCN), some thalamic nuclei, Purkinje cells of cerebellum, sensory and motor nuclei of the brain stem and spinal cord.…”
Section: Introductionmentioning
confidence: 99%